2006
DOI: 10.1182/blood-2006-07-032557
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Livin, an antiapoptotic protein, is an independent favorable prognostic factor in childhood acute lymphoblastic leukemia

Abstract: Livin, a member of the inhibitor of apoptosis proteins, has been considered to be a poor prognostic marker in malignancies. However, little is known about the clinical relevance of Livin expression in childhood acute lymphoblastic leukemia (ALL). In this study, the expression of Livin was analyzed in 222 patients with childhood ALL using quantitative reverse transcriptase-polymerase chain reaction (RT-PCR) to investigate a possible association with the clinical features at diagnosis and treatment outcomes. Bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
58
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 46 publications
0
58
2
Order By: Relevance
“…Caspase activity can be inhibited by a range of cellular processes, such as high expression of Melanoma Inhibitor of Apoptosis Protein, overexpression of survivin, or even by binding of p21 WAF1 to procaspase-3. [43][44][45] T-ALL PDX cells were also sensitive to the death inducing effects of vorinostat, as determined by significantly lower IC 50 values compared to BCP-ALL PDXs. In comparison, the p21 WAF1 -defective T-ALL and p21 WAF1 -functional BCP-ALL PDXs demonstrated generally similar sensitivities to the p53-inducing agents, etoposide and nutlin-3.…”
Section: Discussionmentioning
confidence: 99%
“…Caspase activity can be inhibited by a range of cellular processes, such as high expression of Melanoma Inhibitor of Apoptosis Protein, overexpression of survivin, or even by binding of p21 WAF1 to procaspase-3. [43][44][45] T-ALL PDX cells were also sensitive to the death inducing effects of vorinostat, as determined by significantly lower IC 50 values compared to BCP-ALL PDXs. In comparison, the p21 WAF1 -defective T-ALL and p21 WAF1 -functional BCP-ALL PDXs demonstrated generally similar sensitivities to the p53-inducing agents, etoposide and nutlin-3.…”
Section: Discussionmentioning
confidence: 99%
“…Livin has been identified as a member of the IAP family [2][3][4]. Its expression spectrum includes melanoma, leukemias, bladder cancer, breast cancer, cervical cancer, nasopharyngeal cancer and lung cancer [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Due to its distinctive enrichment in tumors but none or low expression in normal tissue, Livin has been proposed as a potential therapeutic target [19]. Several reports helped to expand its expression profile to variant tumors such as melanoma, leukemias, bladder, breast, cervical, nasopharyngeal and lung cancer [5][6][7][8]. However, there are only limited reports regarding its expression in CRC except some preliminary studies [17][18][19][20][21].…”
mentioning
confidence: 99%
“…More recently, however, livin expression was also detected in various additional cancers, including leukaemias (Qiuping et al, 2004;Choi et al, 2007), bladder cancer (Gazzaniga et al, 2003), lung cancer (Tanabe et al, 2004;Hariu et al, 2005;Crnković-Mertens et al, 2006b), neuroblastoma (Kim et al, 2005), nasopharyngeal carcinoma (Xiang et al, 2006), astrocytoma (Liu et al, 2006), malignant pleural mesothelioma (Gordon et al, 2007), pancreatic cancer (Lopes et al, 2007), and renal cell carcinoma (RCC) (Crnković-Mertens et al, 2007). Notably, studies of biopsies from bladder cancer (Gazzaniga et al, 2003), lung cancer (Hariu et al, 2005), nasopharyngeal carcinoma (Xiang et al, 2006), malignant pleural mesothelioma (Gordon et al, 2007), and pancreatic cancer (Lopes et al, 2007) reported that Livin is typically expressed in the tumour samples, but not in the corresponding normal tissues.…”
mentioning
confidence: 99%